2013
DOI: 10.1111/nph.12441
|View full text |Cite
|
Sign up to set email alerts
|

On the importance of balancing selection in plants

Abstract: Summary Balancing selection refers to a variety of selective regimes that maintain advantageous genetic diversity within populations. We review the history of the ideas regarding the types of selection that maintain such polymorphism in flowering plants, notably heterozygote advantage, negative frequency-dependent selection, and spatial heterogeneity. One shared feature of these mechanisms is that whether an allele is beneficial or detrimental is conditional on its frequency in the population. We highlight exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
166
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(170 citation statements)
references
References 128 publications
2
166
0
Order By: Relevance
“…Recent landscape genetic studies came closer to analysing the causes of microgeographic genetic variation; nevertheless, the conceptual frame of reference of landscape genomics is to compare distinct populations sampled across a gradient or in contrasting environments, rather than looking at within-stand variation, and thus cannot help explain intrapopulation patterns. Yet, plant population biologists have known for long that the distribution of plant species, phenotypes and genotypes can be shaped by stark environmental contrasts even at very short spatial scales: Janis Antonovics et al have published a long series of articles both from the theoretical (Dickinson and Antonovics 1973) and the empirical point of view on heavy metal tolerance in Anthoxanthum odoratum at local scales (Antonovics 2006 and all the previous papers of the "Evolution in closely adjacent plant populations" series quoted therein); oat (Avena barbata) was also the target of similar studies, based on isozyme data (Hamrick and Allard 1972); the long-term Park Grass Experiment has shown microgeographic adaptation in-themaking (Gould et al 2014); the "Evolutionary Canyon" was the subject of several studies on microsite adaptation to moisture gradients at the molecular level, mostly on cereal plants (Li et al 2000 and citations therein); more recently, Delph and Kelly (2014) provided an interpretation of plant intrapopulation genetic diversity as clearly adaptive; and Pannell and Fields (2014) explicitly highlighted local scale processes in their recent review on local adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Recent landscape genetic studies came closer to analysing the causes of microgeographic genetic variation; nevertheless, the conceptual frame of reference of landscape genomics is to compare distinct populations sampled across a gradient or in contrasting environments, rather than looking at within-stand variation, and thus cannot help explain intrapopulation patterns. Yet, plant population biologists have known for long that the distribution of plant species, phenotypes and genotypes can be shaped by stark environmental contrasts even at very short spatial scales: Janis Antonovics et al have published a long series of articles both from the theoretical (Dickinson and Antonovics 1973) and the empirical point of view on heavy metal tolerance in Anthoxanthum odoratum at local scales (Antonovics 2006 and all the previous papers of the "Evolution in closely adjacent plant populations" series quoted therein); oat (Avena barbata) was also the target of similar studies, based on isozyme data (Hamrick and Allard 1972); the long-term Park Grass Experiment has shown microgeographic adaptation in-themaking (Gould et al 2014); the "Evolutionary Canyon" was the subject of several studies on microsite adaptation to moisture gradients at the molecular level, mostly on cereal plants (Li et al 2000 and citations therein); more recently, Delph and Kelly (2014) provided an interpretation of plant intrapopulation genetic diversity as clearly adaptive; and Pannell and Fields (2014) explicitly highlighted local scale processes in their recent review on local adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations are likely to be rare and most mutations are neutral or deleterious, but in some instances the new alleles can be favored by natural selection and/ or genetic drift leading to differences in the genetic structure of populations of different habitats. Natural selection can also maintain genetic variation in balanced polymorphisms which may occur when heterozygotes are favored or when selection is frequency dependent on certain habitat (Delph & Kelly, 2014).Accordingly, it can be suggested that the genetic diversity of Phlomis aurea which is endemic and endangered species, should be conserved in SKP through in situ or/and ex situ technologies. Storing seeds or any type of available germ plasm for conservation from different maternal plants separately in seed banks is a must to restore all variations of the gene structure of this endemic endangered species.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings postulate also that LRRs of LRR-RSTKs exhibit signs of positive selection. Such a selective mode is promoting a rapid alteration of gene sequences in different alleles or species by a non-directional mode without altering the main functions, which in cases of fungal attacks, often increases the reservoir of the ligands that can be recognized in these interactions (Delph and Kelly, 2014).Positive selection on NBS-containing gene families in plants and especially among their LRRs domains, were reported in various studies Perazzolli et al, 2014;Khan et al, 2015), supporting the view that selection upon them for durable disease resistance might be a crucial component of nearly all plant breeding programs (Mace et al, 2014). Comparative analyses among Rosaceae trees species regarding their resistance (R) genes have revealed that solvent-exposed residues of the LRRs domains are hyper-variable, with intensive positive selective pressures acting on them (Perazzolli et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the evolution patterns of plant LRRs-containing genes appears to be rather a complex process (Sekhwal et al, 2015;Zhou et al, 2004), where signatures of positive selective pressures acting upon them are often quite evident (Khan et al, 2015). Positive selection is defined as the rapid fixation of beneficial non-synonymous mutations and is an important evolutionary force for a number of defense-related genes towards their functional diversification, which may be selectively favored in plants under intensive biotic pressures (Delph and Kelly, 2014). Even, the location of positively selected amino acid residues is crucial for obtaining novel gene functions (Mondragon-Palomino et al, 2002); Thus, previous studies have reported that solvent-exposed regions of the LRRs repeats are under strong positive selection.…”
Section: Introductionmentioning
confidence: 99%